The impact of agricultural information services on farm household outcomes in sub-Saharan Africa: A systematic review protocol - Walelign, Solomon Zena; Akalu, Lingerh Sewnet; Siltanu, Gebretsadik Teshager; Bosire, Caroline K.; Mukherji, Aditi (CGIAR System Organization, 2024)
Farmers in Sub-Saharan Africa (SSA) are highly vulnerable to climate variability and extreme weather events due to their reliance on rain-fed farming. Timely access to Agricultural Information Services (AIS) can enhance farmers’ well-being and agricultural productivity by promoting the adoption of climate-smart agricultural practices, improving their ability to manage weather-related risks, and enabling the efficient use of inputs such as fertilizers and seeds. This study aims to evaluate the impact of AIS on agricultural productivity and welfare of farmers in Sub-Saharan Africa. The analysis will synthesize evidence from published studies sourced from bibliographic databases such as Web of Science, Scopus, and CAB Abstracts, as well as grey literature from Google Scholar, ProQuest, and CGIAR’s CGSpace. The screening process will be carried out in Rayyan.ai based on a detailed inclusion and exclusion criteria. Both narrative synthesis and meta-analysis will be used to comprehensively synthesize the evidence. The findings of this study will inform policymakers and extension service providers about the effectiveness of AIS in improving the lives and livelihoods of smallholder farmers in Sub-Saharan Africa.